Ultrasonographic findings in primary umbilical endometriosis - Giovanni Genovese; Emanuela Passoni; Stefano Veraldi; Gianluca Nazzaro (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Primary cutaneous endometriosis is a rare condition. It appears without a prior history of surgical procedure and the umbilicus is the most frequently involved area. Primary umbilical endometriosis, or Villar's nodule, usually presents as a painful nodule. Its differential diagnosis may be challenging. Although histopathological assessment represents the gold standard for diagnosis, cutaneous ultrasonography may be useful in guiding the surgical treatment. Ultrasonographic features of cutaneous endometriosis have not yet been fully explored in the literature. Hence, we report peculiar ultrasonographic findings of primary umbilical endometriosis